Konsep Pendidikan Multikultural di Pesantren Ar-Raudlatul Hasanah - Anggara, Rudiansyah; Nasution, Mhd. Irfan; Hanum, Azizah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to discuss the concept of multicultural education at the Ar-Raudlatul Hasanah Islamic boarding school. The research method used is Library Research (literature study), which involves activities related to collecting library data, reading and taking notes and processing research materials. The results of the study show that multicultural education is being implemented at the Ar-Raudlatul Hasanah Islamic boarding school, both formally and informally. Several books on religious diversity are taught in the Arabic-language book Muqoronatul Adyan, which is specifically taught to 5th grade KMI students who are considered capable of understanding the subject. Similarly, informal activities such as Aneka Ria Nusantara, Drama Arena, and Panggung Gembira clearly teach the importance of understanding differences in ethnicity, race, culture, and religion. The dormitory grouping system also combines all students from different regions in one room, so they can truly embrace multicultural values.